TPM Maintenance Management Model Focused on Reliability that Enables the Increase of the Availability of Heavy Equipment in the Construction Sector - Palomino-Valles, A. (2020)
The purpose of this paper is to present a maintenance study focused on total productive maintenance (TPM) and reliability-centered maintenance (RCM). Its approach is based on the first pillars of TPM, preventive and autonomous maintenance, as well as the FMEA analysis of RCM for maintenance analysis, which was conducted in this study. The implementation of TPM was successful in that various preventive maintenance (PM) policies assigned to the assets were implemented and it was demonstrated that TPM application in the construction industry could reduce the excessive accumulation of maintenance with the same effective optimization, and with support from RCM analysis and its heavy equipment systems analysis. Excessive corrective maintenance accounts for high investment and delay rates in work times of the assigned project. Traditional methods of availability guarantee, such as reactive or routine maintenance, are insufficient to satisfy a heavy equipment maintenance plan; therefore, what is called for is the systematic application of RCM and TMP because they allow the selection and application of effective PM tasks. An approach that develops and thoroughly analyzes the strategies of continuous corrective and PM is used with an atmosphere of uncertainty and with operational data limited by criticism. Results show a 90% improvement in availability.